The Effect of Number of Hotels, Number of Restaurants, Per Capita Income, and Population on Original Local Revenue in East Java Province - Azzahra Mubyaring Putri Sayekti; Riko Setya Wijaya (PT FORMOSA CENDEKIA GLOBAL, 2023)
Original Local Government Revenue of East Java Province makes a high contribution compared to other provinces in Indonesia, being ranked third largest. During the period from 2010 to 2019, there was a continuous increase in Original Local Government Revenue. However, in 2020 there was a decrease due to the COVID-19 pandemic. An increase in Original Local Government Revenue will occur again in 2021 due to the implementation of the new normal policy. The objective of this study is to comprehend and examine how the quantity of hotels, restaurants, individual income, and population size impact the Original Local Government Revenue within the region of East Java Province. This study uses a quantitative approach and focuses on East Java Province from 2010 to 2022. The results show that the number of hotels and restaurants does not affect Original Local Government Revenue. Nonetheless, both individual income per person and population size exert a favorable impact on the Original Local Government Revenue in East Java.